2021
DOI: 10.1002/mnfr.202001068
|View full text |Cite
|
Sign up to set email alerts
|

Impact of Rapeseed and Soy Lecithin on Postprandial Lipid Metabolism, Bile Acid Profile, and Gut Bacteria in Mice

Abstract: Scope Synthetic emulsifiers have recently been shown to promote metabolic syndrome and considerably alter gut microbiota. Yet, data are lacking regarding the effects of natural emulsifiers, such as plant lecithins rich in essential α‐linolenic acid (ALA), on gut and metabolic health. Methods and Results For 5 days, male Swiss mice are fed diets containing similar amounts of ALA and 0, 1, 3, or 10% rapeseed lecithin (RL) or 10% soy lecithin (SL). Following an overnight fast, they are force‐fed the same oil mixt… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
10
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
7
1
1

Relationship

1
8

Authors

Journals

citations
Cited by 17 publications
(10 citation statements)
references
References 61 publications
0
10
0
Order By: Relevance
“…To the best of our knowledge, there are only two other studies to date that have also investigated the impact of soy lecithin on the gut microbiota. The first study tested the effect of 5 days of soy and rapeseed lecithin consumption in Swiss Webster mice and found that the additive increased the abundance of Faecalibacterium prausnitzii non-significantly, regardless of dose or origin [46].…”
Section: Discussionmentioning
confidence: 99%
“…To the best of our knowledge, there are only two other studies to date that have also investigated the impact of soy lecithin on the gut microbiota. The first study tested the effect of 5 days of soy and rapeseed lecithin consumption in Swiss Webster mice and found that the additive increased the abundance of Faecalibacterium prausnitzii non-significantly, regardless of dose or origin [46].…”
Section: Discussionmentioning
confidence: 99%
“…Glycerol-monolaurate can promote dysbiosis in mice fed with a low-dose supplementation in a low-fat diet but can improve high-fat diet (HFD)-induced gut microbiota dysbiosis, increasing abundances in Bacteroides uniformis, Akkermansia, Bifidobacterium, and Lactobacillus and reducing levels of E. coli, Lactococcus [109,110]. Other emulsifiers such as rapeseed lecithin and soy lecithin can increase levels of butyrate production bacteria such as Clostridium leptum [111]. In predisposed or diagnosed IBD patients, the consumption of food products containing glycerol-monolaurate cannot aggravate microbial variations associated with IBD such as increased levels of E. coli and a decreased abundance of Bifidobacterium.…”
Section: Emulsifiers Gut Microbiota and Ibdmentioning
confidence: 99%
“…Interestingly, a recent mice model study investigated the effect of rapeseed lecithin and soy lecithin on gut microbiota [ 92 ]. The consumption of lecithin significantly increased the fecal abundance of Clostridium leptum , regardless of origin or dose.…”
Section: Not All So Bad: Emulsifiers To Date Considered Safementioning
confidence: 99%